2013
DOI: 10.4049/jimmunol.1203260
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evaluation of a Mimicry-Recognizing Paratope: Plasticity in Antigen–Antibody Interactions Manifests in Molecular Mimicry

Abstract: Molecular mimicry manifests antagonistically with respect to the specificity of immune recognition. However, it often occurs because different Ags share surface topologies in terms of shape or chemical nature. It also occurs when a flexible paratope accommodates dissimilar Ags by adjusting structural features according to the antigenic epitopes or differential positioning in the Ag combining site. Toward deciphering the structural basis of molecular mimicry, mAb 2D10 was isolated from a maturing immune respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…The relevance of such approach was demonstrated by Pincus and collaborators (12) who demonstrated that peptides mimicking group B Streptococcus polysaccharide may provide active, protective immunization against the bacteria. However, as demonstrated here and by others (44,45) the interaction of mimetic peptides and the carbohydrate with the target antibody may differ significantly. Moreover, as demonstrated in this study, mimetic peptides characterized by different primary structure differ significantly in their interaction modes.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The relevance of such approach was demonstrated by Pincus and collaborators (12) who demonstrated that peptides mimicking group B Streptococcus polysaccharide may provide active, protective immunization against the bacteria. However, as demonstrated here and by others (44,45) the interaction of mimetic peptides and the carbohydrate with the target antibody may differ significantly. Moreover, as demonstrated in this study, mimetic peptides characterized by different primary structure differ significantly in their interaction modes.…”
Section: Discussionsupporting
confidence: 57%
“…Two principle mechanisms were proposed by Johnson and Pinto (14): structural mimicry, whereby the peptide presents a similar arrangement of functional groups as the carbohydrate, and functional mimicry, whereby the peptide utilizes an alternative binding mode to that of the carbohydrate. Comparative analysis of a limited number of available crystal structures of antibody Fab fragments in complex with mimicking peptides and relevant carbohydrates (44,45) indicates that the actual mechanism is best described as partial structural mimicry. However, a more definitive conclusion awaits characterization of a wider variety of examples (14).…”
Section: Discussionmentioning
confidence: 99%
“…The binding of environmental BPA to host protein may lead to self-tissue, antigen-antibody interactions associated with environmentally induced molecular mimicry. Autoimmune molecular mimicry requires the similarities of surface topologies leading to antigenic combining sites [72]. The binding of BPA to PDI in host has the potential to lead to new protein epitope activation of autoimmunity (Figure 10).…”
Section: Bpa-binding Protein: a Potential New Epitopementioning
confidence: 99%
“…The overall structure exhibits standard immunoglobulin fold topology (Figure a). The structure of scFv 2D10 in disaccharide (α1‐6 mannobiose) complex superimposed well with that in the monosaccharide complex (0.36 Å RMSD) and variations in CDRs were observed in the range from 0.30‐0.77 Å implying minor rearrangements of CDR residues, mainly in CDRL1.…”
Section: Figurementioning
confidence: 78%
“…The α‐mannopyranoside binds to the scFv 2D10 at the centre of the antigen‐combining site . The comparison of α1‐6 mannobiose with me‐α‐D‐mannopyranoside bound scFv 2D10 structures revealed, to our surprise, that the disaccharides do not interact with the antibody where monosaccharide was observed to bind.…”
Section: Figurementioning
confidence: 99%